Pengaruh Lingkungan Kerja dan Beban Kerja Terhadap Kepuasan Kerja Karyawan pada Bank Syariah Nasional (BSN) Kantor Cabang Makassar - Nur Athifah Wahyuningsih; Agung Widhi Kurniawan; Anwar Anwar; Muhammad Ichwan Musa; Uhud Darmawan Natsir (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2026)
This study aims to analyze the influence of the work environment and workload on employee job satisfaction at the Makassar Branch Office of Bank Syariah Nasional (BSN). This study employed a quantitative approach with a descriptive research design. The population consisted of all 80 employees of the Makassar Branch Office of Bank Syariah Nasional (BSN). A total of 49 respondents were selected using a purposive sampling technique. Primary data were collected through a structured questionnaire, while the data were analyzed using multiple linear regression with the assistance of Statistical Product and Service Solutions (SPSS) version 25. Prior to hypothesis testing, the data were subjected to validity, reliability, and classical assumption tests to ensure the accuracy and reliability of the research findings. The findings indicate that the work environment does not have a significant effect on employee job satisfaction. In contrast, workload has a positive and statistically significant effect on employee job satisfaction. Furthermore, the simultaneous test demonstrates that the work environment and workload jointly have a positive and significant influence on employee job satisfaction, indicating that the proposed research hypotheses are supported. These findings suggest that effective workload management plays a more important role in improving employee job satisfaction than the work environment in the context of the Makassar Branch Office of Bank Syariah Nasional. Therefore, management is encouraged to optimize workload distribution while continuously maintaining a supportive work environment to enhance employee job satisfaction.